Coagulation Impairment in Type 2 Diabetes Mellitus - Karim, Fayeza; Akter, Qazi Shamima; Jahan, Shamima; Khanom, Afruza; Haque, Samira; Yeasmin, Tania; Siddika, Tashfia; Sinha, Susmita (Journal of Bangladesh Society of Physiologist, 2015)
Background: Complication of diabetes mellitus (DM) includes coagulation impairment. Hypercoagulable state in patient with DM may accelerate thromboembolic risk for cardiovascular disease (CVD). Objective: To assess Prothrombin Time and Activated Partial Thromboplastin Time in type 2 diabetes mellitus for observing their coagubility status. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2013 to June 2014. One hundred male patients with type 2 diabetes mellitus aged 40-60 years and one hundred age, BMI matched healthy subjects were included as control in this study. Patients were selected from BIRDEM, Dhaka. Prothrombin Time (PT), Activated Partial Thromboplastin Time (APTT) were estimated by auto analyzer. For statistical analysis unpaired studentt test was used. Results: In this study PT and APTT were significantly (P<0.001) lower in diabetes mellitus than those of control group. Conclusion: From this study, it may be concluded that diabetic patients are prone to develop coagulation impairment. Bangladesh Soc Physiol. 2015, June; 10(1): 26-29